Cervical cancer biomarker screening based on Raman spectroscopy and multivariate statistical analysis - Fan, Qiwen; Ding, Hongli; Mo, Huixia; Tang, Yishu; Wu, Guohua; Yin, Longfei (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2024)
[Display omitted] •Multivariate analysis methods were employed to establish diagnostic models.•PLS-DA demonstrated superior classification performance between cancer and normal individuals compared to PCA-SVM and OPLS-DA models.•A hybrid feature selection strategy incorporating PLS-DA and RF models was utilized to identify potential biomarkers.•D-mannose of V (C-N) could potentially serve as a spectral biomarker for cervical cancer. Cervical cancer (CC) stands as one of the most prevalent malignancies among females, and the examination of serum tumor markers(TMs) assumes paramount significance in both its diagnosis and treatment. This research delves into the potential of combining Surface-Enhanced Raman Spectroscopy (SERS) with Multivariate Statistical Analysis (MSA) to diagnose cervical cancer, coupled with the identification of prospective serum biomarkers. Serum samples were collected from 95 CC patients and 81 healthy subjects, with subsequent MSA employed to analyze the spectral data. The outcomes underscore the superior efficacy of Partial Least Squares Discriminant Analysis (PLS-DA) within the MSA framework, achieving predictive accuracy of 97.73 %, and exhibiting sensitivities and specificities of 100 % and 95.83 % respectively. Additionally, the PLS-DA model yields a Variable Importance in Projection (VIP) list, which, when coupled with the biochemical information of characteristic peaks, can be utilized for the screening of biomarkers. Here, the Random Forest (RF) model is introduced to aid in biomarker screening. The two findings demonstrate that the principal contributing features distinguishing cervical cancer Raman spectra from those of healthy individuals are located at 482, 623, 722, 956, 1093, and 1656 cm−1, primarily linked to serum components such as DNA, tyrosine, adenine, valine, D-mannose, and amide I. Predictive models are constructed for individual biomolecules, generating ROC curves. Remarkably, D-mannose of V (C-N) exhibited the highest performance, boasting an AUC value of 0.979. This suggests its potential as a serum biomarker for distinguishing cervical cancer from healthy subjects.